Laparoscopic high anterior resection for triple colorectal cancers with persistent ascending and descending mesocolons: A case report. Issue 3 (21st August 2018) - Hisano, Kyoko; Ueki, Takashi; Kono, Hiroshi; Ikenaga, Naoki; Maeyama, Ryo; Konomi, Hiroyuki; Okido, Masayuki; Yamashita, Nobuaki; Motoshita, Junichi; Ichimiya, Hitoshi
Abstract: Persistent mesocolon is an embryological anomaly of the colon resulting from failure of the primitive dorsal mesocolon to fuse with the parietal peritoneum. We herein present a case of laparoscopic high anterior resection for triple colorectal cancers with persistent ascending and descending mesocolons and a right‐bound inferior mesenteric artery. Preoperative 3‐D CT demonstrated that the sigmoid colon had shifted to the right abdomen and was located under the ascending colon. Moreover, the inferior mesenteric artery and vein traveled toward the right abdomen accompanied by the mesentery of the descending colon. Adhesiolysis between the ascending and sigmoid colon was initially performed, and the sigmoid colon was placed in its normal position. The inferior mesenteric artery was then divided with lymph node dissection using a medial approach, and high anterior resection was completed. An understanding of the anatomical characteristics of persistent mesocolon is important to ensure safe laparoscopic surgery.